HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN KELELAHAN PADA PENGEMUDI BUS CV. PO SAFA MARWA SUNGAI PENUH 2019 - Dina Waldani (Ensiklopedia of Journal, 2020)
Bus driver CV. PO Safa Marwa is known for complaints of fatigue with some symptoms such as back pain, leg and neck aches, sleepy eyes, lack of concentration, lethargy and decreased level of alertness that can cause accidents as well as poor road conditions and bad weather. The purpose of this study is to determine the relationship of body mass index with fatigue in CV bus drivers. PO Safa Marwa. The design of this study is analytic. This research was conducted at CV. PO Safa Marwa. The population in this study were all CV drivers. PO Safa Marwa as many as 64 people with cross sectional techniques. The research measuring instrument uses a questionnaire with data analysis using univariate and bivariate analysis, namely by processing data using a computerized system using the SPSS program version 24.0. The results obtained by more than half (56.2%) of drivers have an abnormal body mass index, more than half ( 67.2%) drivers experience fatigue and drivers who experience more fatigue have an abnormal body mass index (86.1%) compared to normal body mass index (42.9%) with the conclusion that Ho is rejected and Ha is accepted there is the relationship of body mass index with fatigue in bus drivers CV. PO Safa Marwa (p = 0.001). The conclusion that there is a relationship between body mass index with fatigue on the bus driver CV. PO Safa Marwa this research became one of the evaluation materials for travel leaders CV. SAFA MARWA to conduct an evaluation of drivers who have an abnormal body mass index (BMI) by anticipating that fatigue does not result in road accidents when driving a travel car, by reminding drivers to be able to adjust their eating patterns properly so that nutritional status can awake.